Intratumoral heterogeneity and clonal evolution in liver cancer - Bojan Losic (Nature Portfolio, 2020)
Immune-mediated selection pressures impact the clonal evolution of tumours. Here, in hepatocellular carcinoma the authors map spatio-temporal interactions between tumor and immune cells, highlighting the regulatory substrate of intra-tumoural heterogeneity that correlates with regional adaptive immune responses.